Linux yourself concept and programming - Singh, Sunil K. (Boca Raton : Chapman & Hall/CRC, 2021)
Numerous people still believe that learning and acquiring expertise in Linux is not easy, that only a professional can understand how a Linux system works. Nowadays, Linux has gained much popularity both at home and at the workplace. Linux Yourself: Concept and Programming aims to help and guide people of all ages by offering a deep insight into the concept of Linux, its usage, programming, administration, and several other connected topics in an easy approach. This book can also be used as a textbook for undergraduate/postgraduate engineering students and others who have a passion to gain expertise in the field of computer science/information technology as a Linux developer or administrator. The word "Yourself" in the title refers to the fact that the content of this book is designed to give a good foundation to understand the Linux concept and to guide yourself as a good Linux professional in various platforms. There are no prerequisites to understand the contents from this book, and a person with basic knowledge of C programming language will be able to grasp the concept with ease. With this mindset, all the topics are presented in such a way that it should be simple, clear, and straightforward with many examples and figures. Linux is distinguished by its own power and flexibility, along with open-source accessibility and community as compared to other operating systems, such as Windows and macOS. It is the author's sincere view that readers of all levels will find this book worthwhile and will be able to learn or sharpen their skills. KEY FEATURES Provides a deep conceptual learning and expertise in programming skill for any user about Linux, UNIX, and their features. Elaborates GUI and CUI including Linux commands, various shells, and the vi editor Details file management and file systems to understand Linux system architecture easily Promotes hands-on practices of regular expressions and advanced filters, such as sed and awk through many helpful examples Describes an insight view of shell scripting, process, thread, system calls, signal, inter-process communication, X Window System, and many more aspects to understand the system programming in the Linux environment Gives a detailed description of Linux administration by elaborating LILO, GRUB, RPM-based package, and program installation and compilation that can be very helpful in managing the Linux system in a very efficient way Reports some famous Linux distributions to understand the similarity among all popular available Linux and other features as case studies
OCLC-licensed vendor bibliographic record.
Keywords: Linux; Operating systems (Computers); COMPUTERS / Computer Architecture; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Operating Systems / General